OVERVIEW OF MOTHER’S KNOWLEDGE ABOUT EXCLUSIVE BREASTFEEDING AND INFANT WEIGHT GROTWH AT THE GROGOL HEALTH CENTER IN JAKARTA - PANGARIBUAN, CAROLINA OCTAVIANA; FARAH, FRANSISKA (Journal Medical Universitas muhammadiyah Makassar, 2025)
Exclusive breastfeeding is first and main food for infants 0-6 months. Exclusive breastfeeding is the provision of breast milk without providing adiitional. Breast milk is rich in carbohydrates, proteins, fats, vitamins and minerals that are important in infant weight growth which can be measured by the WHO weight-for-age curve. Weight is appropriate for age if the line is <2SD sd - 2SD. This study aims to determine the effect level of maternal knowledge about exclusive breastfeeding on infant weight growth. Cross sectional observational analytic research was conducted at Puskesmas Grogol Petamburan in March-April 2025 on 83 subjects. Subject selection used non-random sampling technique. Inclusion criteria were mothers who have children age of 0 and 6 months at Puskesmas Grogol. Mothers who gave formula milk to their babies were the exclusion criteria. The study has been completed with permission and ethical review of research. Data were collected by measuring body weight, direct interviews, and previous weight data from the Maternal and Child Health book. Weight data was measured using the WHO BB/U curve and then processed with SPSS with other data. The statistical test used was chi-square. Exclusive breastfeeding knowledge level was good 63.9% and not good 37.3%. Infants with age-appropriate weight 53% and overweight 36.1%. There was a significant relationship between the level of maternal knowledge about exclusive breastfeeding and infant weight growth (p value 0.034) and prevalence risk ratio (PRR) 1.567. The conclusion of this study is that maternal understanding of exclusive breastfeeding is important in infant weight growth.